Optimalisasi Biaya Pelaksanaan Proyek Sumitra Hotel dan Resort Melalui Value Engineering - Sintya Rani, Ni Made; Suryawan, Kadek Adi; Yuliana, Ni Putu Indah (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
One of the most important elements influencing a building project's success is its implementation cost. Issues including ineffective material utilization, inept resources, and improper work method selection frequently arise during project execution. These problems may cause projects to be executed with significant time and expense overruns. Project cost control can be used to lessen these issues. Value engineering analysis is the research methodology employed. Value engineering is used to maximize project budgets by locating and removing wasteful spending. Optimizing building projects in terms of time, money, technology, and creativity is the goal of this study. Price surveys serve as the major means of gathering data for the descriptive quantitative research design. Project managers and material suppliers are among the respondents. The Unit Price Analysis (AHSP) and the Budget Plan (RAB) are two examples of secondary data that were employed. The best alternative design and the least expensive alternative design are the two categories into which alternative designs are divided based on the analysis results. The cheapest option's cost optimization is 9.95%, or Rp1,336,499,405, of the initial design cost, whereas the best option's is 9.14%, or Rp1,222,120,406..